A Manual for Moral Collectives: Our Shared Responsibility to End Plastic Pollution, Protect Human Health, and Advance Social Justice for All - James F. Keenan, SJ (Journal of Moral Theology)
This chapter critically discusses the essays that compose the volume. Regarding the production and use of plastics, it shows how the volume provides readers with a manual that supports groups moving toward organizing for social changes.